Disseminated Intravascular Coagulation in Experimental Heatstroke - Rosenthal, T; Shapiro, Y; Seligsohn, U; Ramot, B (Thrombosis and Haemostasis, 1971)
Heatstroke was induced experimentally in dogs, in order to clarify the mechanism of haemorrhage in that disorder.Controls were provided both by dogs subjected to maximal effort at normal ambient temperatures and by dogs exposed to high enviromental temperature without exercise.It was found that above a critical temperature (43.3° C), dogs show a typical clinical and laboratory picture of heatstroke, similar to that occurring in human beings.Quick value and platelets dropped markedly, as did most of the clotting factors including factor V, II, VII and X.Factor VIII was sometimes raised, but also fell terminally. Significant fibrinolysis and shortened half life of labelled fibrinogen were further strong indications of general defibrination.The post-mortem presence of thrombi, provided confirmatory evidence of diffuse intravascular clotting (consumption coagulopathy).